Karangkraf PM Edar Sdn. Bhd.: a suggestion for profit maximisation programme / Azizan Abd. Latif ... [et al.] - Abd. Latif, Azizan; Yaacob, Hamidi; Othman, Zulkipli; Jais, Jamali; Khalil, Mohd Ikhwan; Syed Hussein, Seripah Noli; Wan Hassan, Wan Idzham (1989)
This project paper on the "KARANGKRAF PM EDAR SDN. BHD. -A SUGGESTION FOR PROFIT MAXIMISATION PROGRAMME" is the product of the semi-collaborated efforts of a group of Credit Management Students, MARA Institute of Technology (MIT) 1979, who are assigned to write a paper on Business Research, to comply with their course requirement. Preparation of the paper was carried out under the supervision of Encik Tahir bin Abd. Hamid, MBA Lecturer in Business Research MIT.